Cytomegalovirus retinitis in HIV‐negative patients – associated conditions, clinical presentation, diagnostic methods and treatment strategy. Issue 7 (25th October 2017) - Shapira, Yinon; Mimouni, Michael; Vishnevskia‐Dai, Vicktoria
Abstract: In recent years, numerous reports have tied cytomegalovirus retinitis (CMVR) with multiple systemic conditions in the absence of human immunodeficiency virus (HIV) or acquired immunodeficiency syndrome (AIDS). These range from reports in apparently healthy individuals, through conditions rendering limited immune dysfunction such as advanced age and diabetes mellitus, and finally severe immune dysfunction such as in haematological and rheumatological conditions. Reports are also emerging, suggesting that induced local ocular immunosuppression is a risk factor for CMVR. We herein present a comprehensive collection of the accumulated findings regarding CMVR in non‐HIV patients. We summarize the spectrum of underlying morbidity that has been associated with CMVR, its clinical presentation, diagnostic methods and treatment choice in the attempt to suggest the optimal treatment strategy in this complicated and diverse patient population which is still currently lacking a consensus.